Ketamine as an Adjunct to Opioids for Acute Pain in the Emergency Department: A Randomized Controlled Trial. (22nd March 2017) - Bowers, Karen J.; McAllister, Kelly B.; Ray, Meredith; Heitz, Corey
Abstract: Objectives: This study had five objectives: 1) to measure and compare total opioid use and number of opioid doses in patients treated with opioids versus ketamine in conjunction with opioids; 2) to measure pain scores up to 2 hours after presentation in the ED patient with pain, comparing standard opioid pain control to ketamine in conjunction with opioids; 3) to compare patient satisfaction with pain control using opioids alone versus ketamine in conjunction with opioids; 4) to monitor and compare side effects in patients treated with opioids versus ketamine in conjunction with opioids; and 5) to identify effect variation between different subgroups of patients, with the purpose of focusing future research. We hypothesized that low‐dose ketamine, compared to placebo, as an adjunctive treatment to opioids would result in better pain control over 2 hours and greater patient satisfaction with pain control; further, this protocol will result in a lower opioid dosage over 2 hours. Methods: This was a randomized, double‐blinded, placebo‐controlled trial at a single academic emergency department evaluating the use of ketamine versus placebo in conjunction with opioids for moderate to severe pain. Subjects with a continued high level of pain after an initial dose of opioid analgesia were randomized to receive either 0.1 mg/kg ketamine or placebo prior to protocol‐based dosing of additional opioid analgesia, if required. Over 120 minutes, subjects were assessed for pain level (0–10), satisfaction with pain control (0–4), side effects, sedation level, and need for additional pain medication. Total opioid dose, including the initial dose, was compared between groups. Results: Sixty‐three subjects were randomized to the placebo group and 53 to the ketamine group. No significant differences were found in demographics between the groups. Patients receiving ketamine reported lower pain scores over 120 minutes than patients receiving placebo (p = 0.015). Total opioid dose was lower in the ketamine group (mean ± SD = 9.95 ± 4.83 mg) compared to placebo (mean ± SD = 12.81 ± 6.81 mg; p = 0.02). Satisfaction did not differ between groups. Fewer patients in the ketamine group required additional opioid doses. More patients reported light‐headedness and dizziness in the ketamine group. Conclusions: Ketamine, as an adjunct to opioid therapy, was more effective at reducing pain over 120 minutes and resulted in a lower total opioid dose as well as fewer repeat doses of analgesia. More side effects were reported in the ketamine group (51% vs. 19%), but the side effect profile appears tolerable.